Glucose-6-P/phosphate translocator2 mediates the phosphoglucose-isomerase1-independent response to microbial volatiles - Gámez-Arcas, Samuel; Muñoz, Francisco José; Ricarte-Bermejo, Adriana; Sánchez-López, Ángela María; Baslam, Marouane; Baroja-Fernández, Edurne; Bahaji, Abdellatif; Almagro, Goizeder; De Diego, Nuria; Doležal, Karel; Novák, Ondřej; Leal-López, Jesús; et al. (Plant physiology, 2022)
In Arabidopsis (Arabidopsis thaliana), the plastidial isoform of phosphoglucose isomerase (PGI1) mediates photosynthesis, metabolism, and development, probably due to its involvement in the synthesis of isoprenoid-derived signals in vascular tissues. Microbial volatile compounds (VCs) with molecular masses of <45 Da promote photosynthesis, growth, and starch overaccumulation in leaves through PGI1-independent mechanisms. Exposure to these compounds in leaves enhances the levels of GLUCOSE-6-PHOSPHATE/PHOSPHATE TRANSLOCATOR2 (GPT2) transcripts. We hypothesized that the PGI1-independent response to microbial volatile emissions involves GPT2 action. To test this hypothesis, we characterized the responses of wild-type (WT), GPT2-null gpt2-1, PGI1-null pgi1-2, and pgi1-2gpt2-1 plants to small fungal VCs. In addition, we characterized the responses of pgi1-2gpt2-1 plants expressing GPT2 under the control of a vascular tissue- and root tip-specific promoter to small fungal VCs. Fungal VCs promoted increases in growth, starch content, and photosynthesis in WT and gpt2-1 plants. These changes were substantially weaker in VC-exposed pgi1-2gpt2-1 plants but reverted to WT levels with vascular and root tip-specific GPT2 expression. Proteomic analyses did not detect enhanced levels of GPT2 protein in VC-exposed leaves and showed that knocking out GPT2 reduced the expression of photosynthesis-related proteins in pgi1-2 plants. Histochemical analyses of GUS activity in plants expressing GPT2-GUS under the control of the GPT2 promoter showed that GPT2 is mainly expressed in root tips and vascular tissues around hydathodes. Overall, the data indicated that the PGI1-independent response to microbial VCs involves resetting of the photosynthesis-related proteome in leaves through long-distance GPT2 action.
Keywords: Proteomics; glukosa-6-fosfát; fosfáty; Arabidopsis; proteiny huseníčku; škrob; Starch; Arabidopsis Proteins; Glucose-6-Phosphate Isomerase; Glucose-6-Phosphate; Glucose; glukosa; glukosa-6-fosfátisomerasa; proteomika; Phosphates